Pengaruh Porositas pada Perubahan Tekanan Campuran Gas CO₂ dan O₂ Terhadap Batuan Slag Nikel - Zulfikri; Dan Mugisidi (Prosiding Seminar Nasional Teknoka, 2025)
Porosity in solid materials plays a crucial role in controlling gas pressure behavior and diffusion, particularly in carbon absorption processes within Carbon Capture and Storage (CCS) systems. This study aims to investigate the effect of porosity variations on pressure changes of CO₂–O₂ gas mixtures in nickel slag rocks as potential carbon-absorbing materials. The research method employed a literature review based on various studies discussing the physicochemical characteristics of nickel slag, carbonation mechanisms, and gas interactions within porous structures. Key parameters analyzed include pore size distribution, channel connectivity, and diffusion rate affecting pressure dynamics during gas–solid reactions. The results indicate that highly porous nickel slag experiences a faster pressure drop due to more intensive carbonation reactions, whereas low porosity limits gas transport and slows the process. In conclusion, porosity is a dominant factor governing pressure dynamics and the efficiency of CO₂ capture in nickel slag materials.